Determinants of host feeding success by Anopheles farauti. (December 2016) - Russell, Tanya; Beebe, Nigel; Bugoro, Hugo; Apairamo, Allan; Cooper, Robert; Collins, Frank; Lobo, Neil; Burkot, Thomas
Abstract Background The proportion of blood meals that mosquitoes take from a host species is a function of the interplay of extrinsic (abundance and location of potential hosts) and intrinsic (innate preference) factors. A mark-release-recapture experiment addressed whether host preference in a population ofAnopheles farauti was uniform or if there were anthropophilic and zoophilic subpopulations. The corresponding fitness associated with selecting different hosts for blood meals was compared by measuring fecundity. Methods The attractiveness of humans for blood meals byAn. farauti in the Solomon Islands was compared to pigs using tent traps. Host fidelity was assessed by mark-release-recapture experiments in which different colour dusts were linked to the host to which the mosquito was first attracted. Outdoor restingAn. farauti were captured on barrier screens and the human blood index (HBI) as well as the feeding index were calculated. The fecundity of individualAn. farauti after feeding on either humans or pigs was assessed from blood-fed mosquitoes held in individual oviposition chambers. Results Anopheles farauti were more attracted to humans than pigs at a ratio of 1.31:1.00. The mark-release-recapture experiment found evidence forAn. farauti being a single population regarding host preference. The HBI of outdoor restingAn. farauti was 0.93 and the feeding index was 1.29.Anopheles farauti that fed on a human host laid more eggs but had a longer oviposition time compared toAn. farauti that had blood fed on a pig. Conclusions One of the strongest drivers for host species preference was the relative abundance of the different host species. Here, An. farauti have a slight preference for humans over pigs as blood meal sources. However, the limited availability of alternative hosts relative to humans in the Solomon Islands ensures a very high proportion of blood meals are obtained from humans, and thus, the transmission potential of malaria byAn. farauti is high.